High-Performance Grouting Mortar Based on Mineral Admixtures - Cong Ma; Yuehu Tan; Erbing Li; Yinsuo Dai; Meng Yang (Advances in Materials Science and Engineering)
A study on high-performance grouting mortar is reported. The common mortar was modified by mineral admixtures such as gypsum, bauxite, and alunite. The effects of mineral admixtures on the fluidity, setting time, expansion, strength, and other properties of mortar were evaluated experimentally. The microstructure of the modified mortar was characterized by X-ray diffraction, scanning electron microscopy, and mercury intrusion porosimetry. Moreover, the expansive performance and strength of the grouting mortar were verified by anchor pullout test. The results show that the best conditions for gypsum-bauxite grouting mortar are as follows: a water-to-binder ratio of 0.3, a mineral admixture content of ~15%, and a molar ratio K of 2. The ultimate bearing capacity of the gypsum-bauxite grouting mortar anchor increased by 39.6% compared to the common mortar anchor. The gypsum-bauxite grouting mortar has good fluidity, quick-setting, microexpansion, early strength, and high strength performances.